2008
DOI: 10.1016/j.neuropharm.2008.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and ventral pallidum dynorphin concentrations are markedly increased in human chronic cocaine users

Abstract: Interest in development of therapeutics targeting brain neuropeptide systems for treatment of cocaine addiction (e.g., kappa opioid agonists) is based on animal data showing interactions between the neuropeptides, brain dopamine, and cocaine. In this autopsied brain study, our major objective was to establish by radioimmunoassay whether levels of dynorphin and other neuropeptides (e.g., metenkephalin, neurotensin and substance P) are increased in the dopamine-rich caudate, putamen, and nucleus accumbens of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…(Note that, in contrast, enkephalin expression is very responsive to antipsychotic/D2 receptor antagonist treatment or dopamine loss (Steiner and Gerfen, 1998)). Importantly, increased dynorphin mRNA and peptide levels have also been demonstrated in human cocaine abusers (Hurd and Herkenham, 1993; Frankel et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…(Note that, in contrast, enkephalin expression is very responsive to antipsychotic/D2 receptor antagonist treatment or dopamine loss (Steiner and Gerfen, 1998)). Importantly, increased dynorphin mRNA and peptide levels have also been demonstrated in human cocaine abusers (Hurd and Herkenham, 1993; Frankel et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…PDYN expression is enhanced in putamen ''patches'' but not in caudate or NAcc of cocaine users, whereas [ 3 H]DYN binding is increased in the caudate relative to controls [277]. Enhanced DYN immunoreactivity in the caudate and ventral pallidum but no changes in the putamen and prefrontal cortex of methamphetamine and cocaine users have been reported [295,296]. Methamphetamine users have decreased DYN immunoreactivity in the NAcc, medial pulvinar thalamic nucleus, and temporal/occipital association cortices [296]; changes not observed in cocaine users [295].…”
Section: Dyn/kor System Alterations In Human Post-mortem Tissuementioning
confidence: 97%
“…Enhanced DYN immunoreactivity in the caudate and ventral pallidum but no changes in the putamen and prefrontal cortex of methamphetamine and cocaine users have been reported [295,296]. Methamphetamine users have decreased DYN immunoreactivity in the NAcc, medial pulvinar thalamic nucleus, and temporal/occipital association cortices [296]; changes not observed in cocaine users [295]. A significant correlation between recent psychostimulant use and PDYN expression in cingulate and dorsal lateral prefrontal cortices has also been reported [280].…”
Section: Dyn/kor System Alterations In Human Post-mortem Tissuementioning
confidence: 99%
“…Although mechanisms underlying D3 upregulation are still unclear, preclinical data suggest that it may result from repeated stimulation of D 1 receptors by dopamine during drug use, leading to the release of brain-derived neurotrophic factor (BDNF), which has, in turn, been linked to increased D 3 expression (Guillin et al, 2001) and was recently shown to be elevated in cocaine dependence in humans (D'Sa et al, 2011) (although it should be noted that no definite data support a causal role for BDNF in addiction, see (Pickens et al, 2011)). D 3 upregulation is thought to occur on GABAergic neurons containing D 1 receptors, substance P, and dynorphin (Frankel et al, 2008), as brain dynorphin concentrations are also elevated in human stimulant use (Frankel et al, 2007(Frankel et al, , 2008Kim et al, 2005). Inhibition of GABA neurons via increased transmission at D 3 could therefore modify the functional system responsible for the output of the limbic striatum, thereby modulating motivation to use drugs (see e.g.…”
Section: Evidence That the D 3 Receptor Is Upregulated In Animal Modementioning
confidence: 99%